Prune belly syndrome - A case report - Rupshikha, D; Phukon, MJ; Kusre, GR; Satyanarayana, N; Sunitha, P (Journal of College of Medical Sciences-Nepal, 2012)
Prune Belly Syndrome (PBS) is a rare congenital anomaly. A male baby was received from the Department of Paediatrics, Assam Medical College hospital which died on the second day of birth. It was a diagnosed case of Prune Belly Syndrome (PBS) due to its flabby abdominal wall ballooning out in flanks and skin creases radiating laterally and downwards from the umbilicus - "Prune" like appearance. It was observed that the baby had congenital absence of abdominal muscles and undescended testis. On dissection, associated defects of urinary tract and gastro intestinal tract, persistent cloaca and preductalcoarctation of aorta were noted. The aetiology of this case owes for an overall mesenchymal defect. DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6709 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 48-52